The Montessori Model and Creativity - Fleming, David J.; Culclasure, Brooke Taylor; Zhang, Daniel (Journal of Montessori Research, 2019)
Prior research has demonstrated that the characteristics of school environments can impact the development of creativity in children. Thus, we explored the construct of creativity in the context of a Montessori environment. We used the Evaluation of Potential Creativity to measure creativity in children during one academic year. The study sample comprised 77 third-grade students at a Montessori public school in the southeastern United States and 71 demographically similar students at a traditional public school. Results show that Montessori students performed somewhat better on the Evaluation of Potential Creativity assessment than similar non-Montessori students did. Subgroup analyses indicate that male Montessori students demonstrated higher creativity than did male non- Montessori students. The findings of this study augment the body of research supporting creative development in Montessori children and suggest that researchers should continue to focus on the measurement of creativity in studies related to the efficacy of the Montessori model.